1990
DOI: 10.1007/bf00400332
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of phenol degradation by Rhodococcus sp. P1 I. Batch cultivation

Abstract: Rhodococcus sp. P1 utilizes phenol as the sole carbon and energy source via the beta-ketoadipate pathway. In batch cultivation, concentrations up to 2.8 g.l-1 phenol were degraded. The highest values for the specific growth rate of 0.32 h-1 were obtained at concentrations near 0.25 g.l-1. At higher concentrations, substrate inhibition was observed, characterized by increases in lag phase and decreasing growth rates. A mathematical expression was proposed to fit the kinetic pattern of phenol inhibition on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…At 50 mg L À1 phenol, a significant lag in biomass growth was observed. Similar phenomenon of inhibition due to high phenol concentration for an actinobacteria strain was reported by Straube et al (1990). Generally, phenol biodegradation by pure cultures of bacteria has been adequately described by substrate inhibition models (Kumaran & Paruchuri, 1997).…”
Section: Biodegradation Of Phenolsupporting
confidence: 72%
“…At 50 mg L À1 phenol, a significant lag in biomass growth was observed. Similar phenomenon of inhibition due to high phenol concentration for an actinobacteria strain was reported by Straube et al (1990). Generally, phenol biodegradation by pure cultures of bacteria has been adequately described by substrate inhibition models (Kumaran & Paruchuri, 1997).…”
Section: Biodegradation Of Phenolsupporting
confidence: 72%
“…The PAHs served as sole sources of carbon and energy b Measured as the decrease in PAH after 2 weeks of incubation (for culture conditions see a). The media contained per litre 250 mg pyrene and 250 mg of the respective compounds 500 mg/l d 200 mg/l 675 lic hydrocarbons, nitroaromatic compounds and polycyclic hydrocarbons (Tarnok 1976;Cain 1981;Straube et al 1990). They have been implicated in the degradation of lignin-related compounds (Rast et al 1980;Eggeling and Sahm 1981) and have frequently been isolated from soil polluted with petroleum (Nesterenko et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…However, at lower phenol concentrations (<1000 mg L −1 ) no or little lag phase was observed for growth and phenol biodegradation by both P. aeruginosa and P. pseudomallei (data not shown). Straube et al [10] reported that at higher phenol concentration (≥250 mg L −1 ), substrate inhibition was observed by increase in lag phase. Also, the lower the initial concentration of phenol in the growth medium, the less time it took to be degraded completely by both P. pseudomallei and P. aeruginosa (data not shown).…”
Section: Biodegradation Of Phenolmentioning
confidence: 97%
“…With a phenol-degrading thermophile Bacillus thermoleovorans, very high specific growth rate (2.8 h −1 ) was measured at 15 mg L −1 phenol concentration, while at higher phenol concentrations (100-500 mg L −1 ) growth rates were less as compared to those at low phenol concentration [9]. Straube et al [10] reported that at higher phenol concentration (≥250 mg L −1 ), substrate inhibition was observed by increase in lag phase and decrease in growth rates. Candida parapsilopsis among 22 species isolated from phenol containing wastewater was found to be capable of growth in a medium with 1000 mg L −1 phenol [11].…”
Section: Introductionmentioning
confidence: 99%